A Deleuzian rethinking of time in healthy lifestyle advice and change. Issue 4 (18th March 2019) - Robson, Martine; Riley, Sarah
Abstract: Time is a powerful but under‐examined element in healthy lifestyle advice, particularly in the promise of stable states of future health achievable through sustained lifestyle change. But such linear, sequential time frames reinforce notions of rational choice, personal control, and responsibility despite common experiences of diet and exercise regimens as non‐linear, effortful, and difficult to maintain. An over‐simplification of time thus contributes to the logic of blame when people fail to achieve healthy lifestyle goals, producing spoiled health identities and abject bodies as people struggle to sustain what can be unsustainable. Addressing these problems, we argue that Deleuze's philosophy offers tools to develop an alternative approach in health promotion. Deleuze affords a conceptualisation of multidimensional, embodied, and affective temporalities of health, which give rise to plural subjectivities and disrupt linear models of time. This framework affords a recognition of multiple time frames, such as histories and imagined futures that form part of a living present and shape lifestyle behaviours and identities. Deleuzian concepts that tie into his philosophy of time and form his process ontology, including monism and rhizomes, affect, becoming, and assemblages, are discussed in relation to health promotion. The article concludes that Deleuze offers a critical theory of time that enables a mapping of the ways that people embody multiplicity, non‐linearity, and fluidity as they negotiate healthy lifestyle advice. His concepts illuminate ways in which people can be oppressed and limited by discourses of healthy living, but also point to new, more affirmative directions for health promotion and healthy lifestyle advice.